The Influence Of Work Environment And Leadership On Employee Performance At The Regional Development Planning Agency (BAPPEDA) Of South Lampung Regency - Santori, Ahyar; Sodirin, Sodirin (Social Sciences Journal, 2025)
The success of an organization in achieving its goals depends largely on the behavior and attitudes of people in synergizing various resources including human resources, natural resources, science and technology. In other words, the success of achieving goals depends on the reliability and ability of the people who operate the work units in the organization. People who play important roles in the organization include leadership elements. In order for organizations to reach a high level of performance, they need to ensure that the work environment supports employees. The work environment is everything around employees that can influence them in carrying out their duties. A pleasant work environment, especially during working hours, will influence employee morale and work excellence so that their performance increases. The research objective in this thesis is to examine the influence of the work environment and leadership on employee performance at the South Lampung Regional Development Planning Agency. This research uses a sampling research method with a total of 64 employees as respondents. Analysis was used using quantitative analysis and data processing using the SPSS program The research results show that the work environment has a positive effect on employee performance with an influence contribution of 33.5%. Furthermore, leadership also has a positive effect on employee performance with an influence contribution of 32.8%. The regression test shows that together there is a positive influence between the Work Environment and Leadership on employee performance. The magnitude of the influence of the two variables X1 and X2 on Y is 38.9%, the remaining 61.1% is influenced by other variables outside this research.